Inhõ Pyka Já, Inhõ Ba Já Djwy Dja Ba Ijôk Me Py o Utà além do que os olhos vêem: etnogênese, Xikrin-Mebêngôkre e a macrorregião de Marabá - MANAÇAS, Mirtes Emilia Almeida (Universidade Federal do Pará, 2013)
Based on theoretical considerations on the concept of Ethnogenesis, this dissertation addresses the process of how the Xikrin Indians remake, restructure, reconfigure and reelaborate their political, social, cultural and economic relations in all areas of their lives, when meeting the ―other‖, initiating a new collective and individual identity. One verifies that since the mythical times and until today, the historical process of the Xikrin versus ―the other‖, may be perceived from the their existing body paintings and ornaments, the first being one of the tools used as defense armament, aiming to maintain, in the best way possible, the existence of their community within their live perspectives.